Flavour alignment of New Physics in light of the (g − 2) μ anomaly - Gino Isidori; Julie Pagès; Felix Wilsch (Journal of High Energy Physics, 2022)
Abstract We investigate the flavour alignment conditions that New Physics (NP) models need to satisfy in order to address the (g − 2) μ anomaly and, at the same time, be consistent with the tight bounds from μ → eγ and τ → μγ. We analyse the problem in general terms within the SMEFT, considering the renormalisation group evolution of all the operators involved. We show that semileptonic four-fermion operators, which are likely to generate a sizeable contribution to the (g − 2) μ anomaly, need to be tightly aligned to the lepton Yukawa couplings and the dipole operators in flavour space. While this tuning can be achieved in specific NP constructions, employing particular dynamical assumptions and/or flavour symmetry hypotheses, it is problematic in a wide class of models with broken flavour symmetries, such as those proposed to address both charged- and neutral-current B anomalies. We quantify this tension both in general terms, and in the context of explicit NP constructions.